Socio-economic issues investigated in an HIV Treatment as Prevention (TasP) trial in rural KwaZulu-Natal: research questions, implementation and progress - (:unkn) unknown (My University, 2013)
BackgroundHIV testing of all adult members of a community, followed by immediate antiretroviral treatment (ART) initiation of HIV-infected participants, regardless of immunological or clinical staging, could prevent onward transmission and reduce HIV incidence. The community cluster-randomized ANRS 12249 Treatment as Prevention (TasP) trial has been designed to test acceptability, feasibility and efficacy of this strategy in Hlabisa sub-district, KwaZulu-Natal. In addition to epidemiological, clinical and operational challenges, TasP raises unprecedented social challenges at individual and population levels.MethodsThe trial began in March 2012. Innovative research tools are being implemented at each stage of the TasP intervention: repeat home-based questionnaires with household heads and individual household members; specific questionnaires for the HIV-infected individuals attending trial clinics and for those who choose not enter HIV care; combined with in-depth semi-structured individual qualitative interviews, repeat focus groups discussions (consumer panels) using participatory methods.ResultsWe will be able to describe precisely participation in the trial and to understand the social determinants of uptake in terms of repeat HIV testing, linkage to and retention in HIV care; the impact of this TasP strategy on quality of life; the economic impact on households and the healthcare system; and consequences for people’s life in terms of HIV disclosure, stigma, sexual behaviours, social support, treatment experience and adherence.ConclusionsTasP is not just a biomedical intervention. Understanding the consequences of implementing universal HIV testing and ART on individual behaviour changes and community social norms is crucial to explain any observe impact on HIV incidence.
Keywords: African Research